Pharmacokinetic and pharmacodynamic evaluations of a 10 mg/kg enrofloxacin intramuscular administration in bearded dragons (Pogona vitticeps): a preliminary assessment. Issue 1 (28th April 2016) - Salvadori, M.; Vercelli, C.; De Vito, V.; Dezzutto, D.; Bergagna, S.; Re, G.; Giorgi, M.
Abstract : Enrofloxacin (E) is commonly used in veterinary medicine. It is necessary to perform pharmacokinetic/dynamic studies to minimize the selection of resistant mutants of bacteria and extend the efficacy of antimicrobial agents. Eight healthy adult Pogona vitticeps were assigned into two groups of equal size and treated with a single intramuscular injection of E at 10 mg/kg. Blood samples were withdrawn at different scheduled times for each group, and rectal swabs were collected. E and ciprofloxacin (active metabolite) blood concentrations were quantified by an HPLC validated method, while the in vitro antimicrobial susceptibility was evaluated by the Kirby–Bauer disc diffusion susceptibility test. The pharmacokinetic profiles of E gave similar pharmacokinetic parameters irrespective of the collection time schedule. Bacteria isolation showed the presence of both E. coli, Salmonella enterica subspecies enterica and subspecies 3a, Proteus spp., and Pseudomonas spp. The majority of isolated colonies were sensitive to E, but the treatment did not reduce the number of bacteria in faeces. Results suggest that E is able to reach blood concentrations high enough to kill susceptible bacteria (MIC < 0.9 μg/mL), but at the same time does not significantly affect intestinal bacteria.